317 Incidence of Cognitive Impairment after Stroke: a Retrospective Cohort of Rehabilitation Patients. (16th September 2019) - Gorey, Sarah; Cassidy, Tim
Abstract: Background: Pendlebury and Rothwell's recent paper reports the incidence of cognitive impairment and dementia post stroke as 5% for TIA, 8% for minor stroke and 34% for severe stroke. 1 We wanted to explore if these trends were reproducible in an Irish cohort. Methods: We conducted a retrospective review of a random sample of 100 discharges from a dedicated stroke rehabilitation unit between 2017 and 2018. Diagnosis of cognitive impairment or dementia was extracted from MDT discharge documentation, along with results of cognitive assessments. This cohort required inpatient rehabilitation post stroke, so we can infer that these were severe strokes. As a surrogate marker of disability, the average Barthel Index of this sample on admission to rehabilitation was 13, indicating moderate functional dependency. Results: Complete information was available for 94/100 patients. The average age was 67 years (age range 33-95 years) 37 of 94 (39%) were judged to have cognitive impairment on discharge. Demonstration of functional impairment was central to this assessment. 30 (81%) of these diagnoses were supported by abnormal cognitive tests. 3 of those judged to have cognitive impairment, were unable to complete cognitive assessment. 2 of those judged to have cognitive impairment had cognitive scores which were within the normal range. None of the discharge letters mentioned a diagnosis of post stroke or vascular dementia. Conclusion: This study replicates Pendlebury and Rothwell's findings that over a third of people suffering from severe strokes will develop cognitive impairment. This is of critical importance to stroke clinicians as it should prompt frank discussions with stroke patients and their families about prognosis, recovery and future planning.